1964
DOI: 10.1111/j.1151-2916.1964.tb15656.x
|View full text |Cite
|
Sign up to set email alerts
|

Grain‐Boundary Diffusion in MgO

Abstract: Grain-boundary diffusion of Ni2+ was investigated in polycrystalline MgO and also in isolated grain boundaries in natural and prepared bicrystals of MgO. Concentration distributions were determined with the aid of both electron microbeam probe spectroscopy and X-ray absorption analysis. Results from diffusion couples in which a surface was maintained at constant concentration during the diffusion annealing indicate that grain-boundary diffusion is the predominant transport mechanism in polycrystalline M g O at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1965
1965
2008
2008

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…No evidence for grain-boundary diffusion in bicrystals of MgO was observed above 1300°C. 4 The precise temperature at which solid solution is complete in a given specimen, however, depends on the type and amount of precipitate in the material.…”
Section: August 1966mentioning
confidence: 99%
“…No evidence for grain-boundary diffusion in bicrystals of MgO was observed above 1300°C. 4 The precise temperature at which solid solution is complete in a given specimen, however, depends on the type and amount of precipitate in the material.…”
Section: August 1966mentioning
confidence: 99%
“…Recent investigations have shown that cation diffusion can be enhanced a t grain boundaries,21s22 and the region oC a grain that may be affected by a boundary may be as large as I O2 to lo4 A. [23][24][25][26] For submicron particles, such as were used in this investigation, a very large volume fraction of a grain may be affected by a boundary. One of the possible reasons Cor the higher diffusion coefficients observed in this study could be the enhancement of cation diffusion by an increase in the boundary layer of fine grains.…”
Section: (3) Pretreated Powdermentioning
confidence: 99%
“…In alkali halides and oxides, however, there are indications that the high diffusivity paths are of considerable dimensions. [6][7][8] In these crystals higherorder approximations have to be taken into account. In the present paper higher-order approximations for the solution of the grain-boundary diffusion problem for an instantaneous source are presented.…”
Section: Introductionmentioning
confidence: 99%